2000
DOI: 10.1002/(sici)1522-2683(20000101)21:1<135::aid-elps135>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

A transmission imaging spectrograph and microfabricated channel system for DNA analysis

Abstract: In this paper we present the development of a DNA analysis system using a microfabricated channel device and a novel transmission imaging spectrograph which can be efficiently incorporated into a high throughput genomics facility for both sizing and sequencing of DNA fragments. The device contains 48 channels etched on a glass substrate. The channels are sealed with a flat glass plate which also provides a series of apertures for sample loading and contact with buffer reservoirs. Samples can be easily loaded i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…There are indications that this new instrumentation might soon become commercially available. In one approach, Simpson et al [84] at CuraGen Corporation (New Haven, CT, USA) have described a new microfabricated channel device containing 48 channels etched on a glass substrate. The bottom plate was made using Borofloat glass, into which 48 channels were etched to a depth of 50 mm.…”
Section: Microfabricated Capillary Arrays (ìCae)mentioning
confidence: 99%
“…There are indications that this new instrumentation might soon become commercially available. In one approach, Simpson et al [84] at CuraGen Corporation (New Haven, CT, USA) have described a new microfabricated channel device containing 48 channels etched on a glass substrate. The bottom plate was made using Borofloat glass, into which 48 channels were etched to a depth of 50 mm.…”
Section: Microfabricated Capillary Arrays (ìCae)mentioning
confidence: 99%
“…The basic design of the separation system is similar to Simpson's design [44]. Briefly, a high-voltage power supply from Bertan (Hicksville, NY, USA) was used to drive electrophoresis.…”
Section: Equipmentmentioning
confidence: 99%
“…Latest developments in microchip electrophoresis have been summarized in recent reviews [8][9][10]. One of the most promising features of microchip electrophoresis (MCE) is its great potential for high-throughput analysis due to the possibility for high-speed separations [11] and the ease of multiplexing the separation channels [12][13][14][15]. We have recently shown that capillary array electrophoresis and MCE have great potential as high-throughput screening (HTS) systems for assaying the enantioselectivity of large libraries of potential catalysts [16].…”
Section: Introductionmentioning
confidence: 99%